New Trends in Islamic Political Parties in the Arab Spring Countries - Ibnu Burdah (Al-Jami'ah: Journal of Islamic Studies, 2014)
The recent developments of Islamic political parties in the Arab spring countries show new orientation and agendas, i.e. reconfirmation of their commitment to democratic values, strengthening civil society, and adopting human rights principles. In the same time, they indicate not to be interested in the old Islamic agendas relating to jihad for Islamic states (dawlah Islāmiyah) and “global Islamic government” under one centralized caliphate (al-khilāfah al-Islāmiyyah). It is the case of Justice and Development Party (Ḥizb al-‘Adālah wa’l-Tanmiyah) in Morocco, Freedom and Justice Party (Ḥizb al-Ḥurriyyah wa’l-‘Adālah) in Egypt, and Awakening Party (Ḥizb al-Nahḍah) in Tunis. This paper seeks to explore and explain this new fact. Based on literary research and interviews with the leaders of the Justice and Development Party (Ḥizb al-‘Adālah wa’l-Tanmiyah) in Morocco, the paper concludes that the new orientation and agendas of Islamic political parties in the Arab spring states are related to democratization in the world, strong waves of Arab spring in many Arab states, and the dynamics of the internal parties.[Perkembangan mutakhir partai-partai politik Islam di sejumlah negara Arab “Musim Semi” menunjukkan adanya perubahan orientasi dan agenda baru, berupa penegasan kembali komitmen mereka terhadap nilai-nilai demokrasi, penguatan masyarakat sipil, dan adopsi prinsip-prinsip hak asasi manusia. Pada saat yang sama, mereka tampak kurang tertarik kepada agenda-agenda politik Islam lama seperti jihad bagi pendirian negara Islam dan pendirian pemerintahan Islam global di bawah satu khalifah yang tersentralisasi. Hal ini relevan terhadap kasus Partai Keadilan dan Pembangunan (Ḥizb al-‘Adālah wa’l-Tanmiyah) di Maroko, Partai Kebebasan dan Keadilan (Ḥizb al-Ḥurriyyah wa’l-‘Adālah) di Mesir, dan Partai Kebangkitan (Ḥizb al-Nahḍah) di Tunisia. Artikel ini berupaya mengeksplorasi dan menjelaskan fakta baru ini. Berdasarkan kajian pustaka dan wawancara dengan sejumlah petinggi Partai Keadilan dan Pembangunan di Maroko, penulis berkesimpulan bahwa orientasi baru ini terjadi akibat dari gelombang demokratisasi dunia, “angin kencang musim semi” Arab yang begitu kuat, dan dinamika internal partai.]